Refractive and Vision Status in Down Syndrome: A Comparative Study - Hassan Hashemi; Shiva Mehravaran; Soheila Asgari; Farzaneh Dehghanian Nasrabadi (Türk Oftalmoloji Dergisi, 2021)

(untitled)
Objectives:To determine the prevalence of refractive errors and visual impairment in Down syndrome (DS) patients compared to normal controls.Materials and Methods:Cycloplegic refraction was tested in 213 DS patients and 184 normal age- and gender-matched controls using autorefraction followed by retinoscopy. Data from the worse eye of each case were used in the analyses.Results:In the DS and control groups, respectively, mean age was 17.2±4.8 and 17.2±4.4 years (p=0.993) and 53.0% and 49.5% were male (p=0.473). In the DS and control groups, respectively, mean spherical equivalent (SE) was -5.13±4.47 and -4.15±3.04 diopters (D) in myopics (p=0.050) and 2.47±1.64 and 2.36±2.04 D in hyperopics (p=0.482), mean cylinder error was -2.17±1.39 and -2.05±1.57 D (p=0.451), mean J0 was -0.03±0.89 and 0.12±0.76 D (p=0.086), and mean J45 was 0.11±1.02 and -0.13±1.03 D (p=0.024). The prevalence of oblique astigmatism was higher in the DS group (20.4% vs. 6.1%) while against-the-rule astigmatism was more prevalent in the control group (84.0% vs. 71.6%) (p<0.001). The prevalence of anisometropia was not significantly different between the groups (19.4% vs. 13.8%). Visual impairment was detected in 11.7% of the DS and 0.5% of the control group (p<0.001). The prevalence of amblyopia was 36.3% and 3.8% in the DS and control groups, respectively (p<0.001). Based on the multiple model, only absolute SE inversely correlated with age and differed between males and females (all p<0.05).Conclusion:In DS patients, the prevalence rates of refractive errors, amblyopia, and visual impairment are higher than those in non-DS individuals, and emmetropization appears to be either defective or slow. Cylinder error is stable in this age range, but the rotation of astigmatism axis is different from normal samples.